Distribution and abundance of meiofauna in intertidal sand substrata around Iceland - Delgado, J.D.; Riera, R.; Monterroso, Ó.; Núñez, J. (Aquatic Ecology, 2009)
Iceland is situated in an important subarctic transition area where complex oceanographic dynamics occur. The intertidal, subtidal, and deep-sea faunal communities of Iceland are being intensively studied, as a critical resource for continued sustainability of fisheries and the preservation of northern littoral ecosystems. However, the meiofaunal communities and the environmental factors affecting them are still relatively poorly known. The meiobenthic metazoan community was studied with core sampling in 23 sandy beaches along the intertidal zone of the Iceland coast in a campaign developed in September 2003. Small-scale variation in meiofauna composition (major taxa) was explored and related to biotic and abiotic factors at different scales, such as beach exposure, granulometry, and organic matter content. Differences in meiofaunal community structure at a low taxonomic resolution appeared among beaches located within wide biogeographical zones of hydrobiological significance (NE and SW Shelf regions) and exposure degrees. Seventeen major taxa were recorded. In contrast with more local and taxon-focused studies, oligochaetes were the dominant group all around Iceland, followed by nematodes, turbellarians, gastrotrichs, and copepods (mainly harpacticoids). Acari, ascidians, bivalves, cnidarians, collembolans, gastropods, isopods, kinorhynchs, insects, nemerteans, ostracods, and polychaetes were relatively scarce groups, together being less than 1.6% of the meiofauna. There was a large variation in meiofaunal abundance between sites. Maximum abundances (>500 ind. cm−2) were found in Sauđarkrökur, Hraunhafnartangi, and Skálaness, whereas minimum abundances (<40 ind. cm−2) were recorded in Magnavík, Jokülsárlón (glacier beach site), Vikurnúpur, Breidalsvík, and Stokknes. We did not find a clear pattern in overall meiofaunal abundance regarding the degree of exposure of beaches. Oligochaetes, nematodes, and copepods were relatively more abundant in sheltered beaches, whereas turbellarians and gastrotrichs ...